(untitled) (Journal of Imam Al-Kadhim College, 2023)
Journalism today, on websites in the era of communication technology, is of great importance to the public because of its major role in conveying news and events as they occur, and no one can deny the role that journalistic arts play in today’s journalism due to the function they perform with speed, ingenuity, and distinctive effectiveness in various fields during transmission. News and events around the world After this great expansion in the number of international and Arab press institutions in general, and Iraqi ones in particular, different journalistic arts appeared at successive time intervals, competing with each other and complementing each other, to increase the press’s chances of success and to increase societies’ need for its functions. The problem of our research lies in knowing the methods of writing journalistic arts on websites. The importance of this research is to know the methods of writing journalistic arts on the website of Al-Sabah newspaper. Because these journalistic arts on websites are closely related to the use of journalistic arts, The objectives of our research were to uncover the prevailing journalistic arts on the website of Al-Sabah newspaper, as well as to know the factors in the development of methods of writing journalistic arts on the website of Al-Sabah newspaper. In order to achieve the objectives of this study, the researcher employed the descriptive approach. The researcher relied on content analysis as a tool for collecting the necessary data. The research reached several results, the most prominent of which are : the report came in first place among the main categories that fall within the journalistic arts of Al-Sabah newspaper, with a number of repetitions amounting to (35) out of a total number of repetitions of (125), with a percentage of (28%). One of the most important conclusions reached by the researcher is that the emergence of the Internet is considered a new way to the media, and it also has an important relationship with both the traditional and electronic press publications, as there are many reasons and justifications for the merger between the two worlds of traditional newspaper publications and the electronic publishing of these newspapers. One of the important recommendations that the researcher touched on is that there is an importance in measuring the public’s opinion in the field of knowing its opinions regarding the journalistic arts. That is, we suggest that Al-Sabah newspaper conduct a survey from time to time in order to know the impact of the journalistic arts on readers, by conducting scientific studies and questionnaires, whereby Measuring the impact of these arts on the public and the extent to which they achieve their desired goals in order to correct their paths and benefit from them in the future.